Improved water solubility of quercetin by preparing complexation with cyclodextrins in binary solvent - Thi Lan, Pham; Long Khanh, Pham; Thi Ngoan, Nguyen; Hai Khoa, Le; Xuan Minh, Vu; Anh Son, Nguyen; Dai Lam, Tran (Vietnam Journal of Biotechnology, 2021)
The antioxidant capacity of polyphenols have been widely used in food and pharmaceutical industries. Quercetin (Quer) is a polyphenolic flavonoid that shows several biological effects such as antioxidant, antitumor, antibacterial and antiproliferative effects both in-vitro and in-vivo. However, the solubility of quercetin in water is poor. Thus, it is essential to improve solubility of quercetin in pharmaceuticals by making its complexation with other compounds. In this study, the synthesis of the 2-hydroxypropyl-β-cyclodextrin complex with quercetin (Quer-HPβCD) in the form of nanoparticles in water-ethanol solvents has been carried out. The results showed that the obtained yield of (Quer-HPβCD) complexation in binary solvent was greater than that in pure water. The highest Y value was 80% in a binary solvent with 20% v/v of ethanol. The composition, morphology, structural and thermodynamic properties of the nanoparticles Quer-HPβCD have been determined. This study demonstrated that using mixed water- ethanol solvent and lyophilization technique was able to produce quercetin nanoparticles with significantly smaller particle size. The nanoparticles have a spherical shape with an average size of about 40-60 nm. The results of the phase solubility diagram showed that in water the solubility of quercetin increased and linearly depended on the concentration of host’s molecule while Quer and HP-βCD obtained a 1:1 stoichiometric complex. The stability constant of (Quer-HPβCD) complex was found to be logK = 2.56. The Gibbs energy change of the complexation reaction was found to be -14.60 kJ/mol.